FAKTOR PENYEBAB PENURUNAN POPULASI MALEO SENKAWOR DI DESA SAUSU PIORE KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Kiky Arista; Abdul Wahid; Moh. Ihsan (Universitas Tadulako, 2016)
Maleo bird is a unique wildlife species, particularly in terms of habitat, as it lives around coastal sands, or in the mountain that having any hot spring around. Sands are needed to lay down their eggs into 15 cm in depth for hatching. Conservation problem faced particularly related to decrease in its population was due to eggs collection and habitat destruction (degradation and fragmentation). Eggs exploitation occurs due to the lack of community awareness. Habitat destruction was cause by forest encroachment and illegal logging while the decrease in the size of habitat was mainly due to forest land conversion and illegal farming. Forest conversion causes forest fragmentation leading to maleo nesting ground isolation. The objective of the research was to identify factors causing the decrease in maleo (Macrocephalon maleo) population at Sausu Piore Village, Parigi Moutong District, Central Sulawesi. Multiple Analysis Regression was used to analysed data applying regression equation of Y = a + b1X1 + b2X2 + b3X3 where Y = maleo presence, a = intercept, X1 = the size of forest (m2), X2 = human presence, X3 = vegetation density, b1, b2, b3 are regression coefficient. The results showed that human presence was significantly influenced the decrease of population, while the size of forest and vegetation density were not. Ttable = 3.182 compared to Tcount = 3.820 where showing that human significantly causes the decrease of the population with correlation coeffision of 87.9%. This means 12.1% due to other factors. The obtained regression equation is Y = 62.119 + 4.865 X. Keywords: maleo, population, Sausu Piore